Carl Schmitt o totalizmie i jego podmiocie. Prolegomena do rozważań o państwie totalitarnym - Kaczorowski, Paweł (Civitas. Studia z filozofii polityki, 2012)
The author attempts to verify whether defining totalitarianism in terms of a state striving to obtain total control over the life of individuals and collectives is a proper approach. Does totalitarianism genuinely imply a society completely subordinated to a state? And, in dealing with the political realities of a totalitarian regime, can we consider a totality other than that created by the state? The author reaches for Carl Schmitt’s reflections on political totality and its subjects. It is thanks to this approach that we are able to look at a totalitarian structure more primal than a state, the structure that is a total society. The author presents a historical and philosophical description of the process of forming a total society, which begins with the discontinuation of the distance between that which falls to the state and that which falls to society.